Searching for Answers: Health Literacy and Digital Navigation in Midlife and Older Adults - Matteya A. Proctor; Carolyn R. Pagán; Samina Rahman; Maureen Schmitter-Edgecombe (The International Journal of Aging and Human Development, 2026)
As digital, internet-based health communication becomes more common, understanding the factors influencing midlife and older adults’ ability to navigate online resources is essential. This study investigated whether health literacy interacts with communication format to affect health search performance. Seventy-eight community-dwelling midlife and older adults classified as having high or low health literacy using the Newest Vital Sign completed a counterbalanced print- and internet-based health search task. A 2 × 2 mixed-factorial analysis of variance revealed that both lower health literacy and the internet format were associated with poorer task accuracy and greater task completion time. Contrary to expectation, the influence of task format on performance did not disproportionately affect individuals with low health literacy. Findings suggest that both health literacy and communication formats independently influence midlife and older adults’ ability to accurately and efficiently retrieve health information. These results underscore the need for digital health literacy assessments and the development of interventions to support access to digital health information among aging adults.